2007
DOI: 10.1083/jcb.200703052
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified biologically active and proteolysis-resistant VEGF-A isoform VEGF111 is induced by genotoxic agents

Abstract: Ultraviolet B and genotoxic drugs induce the expression of a vascular endothelial growth factor A (VEGF-A) splice variant (VEGF111) encoded by exons 1–4 and 8 in many cultured cells. Although not detected in a series of normal human and mouse tissue, VEGF111 expression is induced in MCF-7 xenografts in nude mice upon treatment by camptothecin. The skipping of exons that contain proteolytic cleavage sites and extracellular matrix–binding domains makes VEGF111 diffusible and resistant to proteolysis. Recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 38 publications
(56 reference statements)
2
82
0
1
Order By: Relevance
“…Delcombel et al demonstrated that VEGF-A111a (a biologically active and proteolysis-resistant isoform 26 ), which contains the exon 8a-encoded sequence, does not bind to NRP1 (Fig. 2 of 9 ).…”
Section: Evidence That the Exon 8a Domain Which Vegf-a121a Has Is Rmentioning
confidence: 99%
“…Delcombel et al demonstrated that VEGF-A111a (a biologically active and proteolysis-resistant isoform 26 ), which contains the exon 8a-encoded sequence, does not bind to NRP1 (Fig. 2 of 9 ).…”
Section: Evidence That the Exon 8a Domain Which Vegf-a121a Has Is Rmentioning
confidence: 99%
“…Other secondary antibodies were purchased from Dako (Glostrup, Denmark). Western blot was performed as previously described [20]. Signals were quantified using the Fluor-S Imager and the Quantity One software (BioRad, Hercules, CA, USA).…”
Section: Chemicals Antibodies Western Blot Immunohistochemistrymentioning
confidence: 99%
“…VEGF 111 a (E1-4 & 8a), an isoform induced by genotoxic stress [20], is resistant to degradation and freely diffusible. By sharp contrast, VEGF 189 a is found immobilized at the cell surface or in the extracellular matrix by its heparin sulfate binding properties [21], and its activity is largely dependent on cleavage in the E5 and E6-derived domains to improve its interaction with VEGF-R1 or -R2 [22].…”
Section: Introductionmentioning
confidence: 99%
“…28 VEGF111 was also identified later as a biologically active and proteolysisresistant splice variant of this family. 32 Pegaptanib, the first anti-VEGF-A agent approved for the treatment of exudative AMD, selectively neutralizes only VEGF165 and is less efficacious than agents that neutralize all isoforms. 33 proteoglycan to chemoattract PDGF receptor-B (PDGFR-b) expressing pericytes.…”
Section: Selection Of a Dvd-ig Molecule With Improved Thermal Stabilitymentioning
confidence: 99%